The Role of Rural Tourism in the Development of Economically Backward Regions, the Example of Georgia - Bestaeva, Salome (European Scientific Journal, ESJ, 2022)
Tourism is the most dynamic direction of the economy, and its role and importance in the world are increasing daily. The growth of the economic, social, and cultural importance of tourism determines the development of individual countries because tourism is a complex business direction, the development of which leads to the possibility of sustainable economic growth.Tourism has many directions, among which is rural tourism. Tourism in rural areas has a special place in developing rural regions and solving socio-economic problems because the local population no longer has to leave the village to get better working and living conditions. It should be noted that, in developed countries, tourism is used as an economic tool in rural areas to solve the problems of mountainous regions and the population living there. In addition to economic benefits, tourism development in rural areas has inestimable importance in preserving rural regions’ cultural and historical identity. Tourism business development in rural areas is very important in recovering the local population. According to the recommendation issued by the United Nations, it is necessary for the population living in the city to spend 3-4 months of rest in nature. The purpose of our research is to study the economic and social problems of the rural population in the example of Adjara, Georgia, as well as to determine the role of rural tourism in solving the problems in rural areas.